PROPOSAL TO DEVELOP AND VALIDATE A MOODLE-BASED FLIPPED LEARNING PLATFORM FOR ENHANCING ARABIC COMMUNICATION SKILLS - Makinde, Semiu Olawale; Atotileto, Abdussalaam Aminu; Sulyman, Mariam Bola (Sanata Dharma University Yogyakarta, 2024)
This research proposes the development and validation of a Moodle-based flipped learning strategy for enhancing basic communication in Arabic among undergraduates in Nigeria, using Al-Hikmah University as a case study. Flipped learning is a model that redefines traditional classroom activities, enhances engagement, and deepens understanding. Integration with Moodle, a widely used Learning Management System (MLS), creates a structured environment for content delivery. The study involves creating Arabic language modules on Moodle, including instructional videos, multimedia, and interactive exercises. These modules support self-paced learning, enabling students to review materials before class, with in-class time dedicated to collaborative activities. Effectiveness will be assessed through quantitative and qualitative measures, including pre- and post-assessment tests, surveys, and focus group discussions. Anticipated outcomes include improved language proficiency, increased participation, and enhanced communication skills. Validating the flipped learning platform using Moodle at Al-Hikmah University will provide valuable insights into language education, particularly for enhancing Arabic communication skills. The study's novelty lies in its innovative use of flipped learning, customized application of Moodle, focus on a unique demographic, and practical approach to language acquisition. This research offers a blueprint for future implementations in diverse educational settings, promoting the broader adoption of technology-enhanced learning methods.